PENGARUH DISIPLIN KERJA DAN MOTIVASI KERJATERHADAP KINERJA ASN MELALUI KEPUASAN KERJA DI DINASPENDIDIKAN DAN KEBUDAYAAN KABUPATEN SITUBONDO - putri, Yuliana; Wahyuni, Ika; Subaida, Ida (Fakultas Ekonomi dan Bisnis, 2022)
The Department of Education and Culture is a government agency that is responsible for all matters relating to education. In charge of carrying out the government affairs of Situbondo Regency in the field of education based on the principle of autonomy and assistance tasks, as well as carrying out other tasks related to education given by the Mayor / Regent in accordance with their field of duty. The purpose of this study was to analyze and examine the effect of work discipline and work motivation on the performance of state civil servants through job satisfaction at the Education and Culture Office of Situbondo Regency. The sampling technique used was saturated sampling technique. Data analysis and hypothesis testing in this study used the Structural Equation – Partial Least Square (PLS-SEM) model. The results of the direct influence hypothesis test using the smart PLS 3.0 application, show that work discipline has a significant effect on job satisfaction, work motivation has a significant effect on job satisfaction, work discipline has a significant effect on performance, work motivation has no significant effect on performance, job satisfaction has a significant effect on performance . The results of the indirect effect hypothesis test show that work discipline on performance through job satisfaction has a significant positive effect, work motivation on performance through job satisfaction has a significant positive effect.